Comparative Assessment of Multiple IaC Tools for Provisioning Emulated SDN Topologies in Cloud Environments - Lima, Vitor Reiel M.; Callado, Arthur C.; Bonfim, Michel S. (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
This paper presents a comparative analysis of multiple Infrastructure as Code (IaC) approaches applied to the provisioning of emulated SDN topologies in cloud environments. The study considers seven widely used tools, evaluated on two SDN topologies with distinct structural characteristics, one symmetric and the other asymmetric. To this end, an experimental evaluation was conducted under controlled conditions, considering metrics related to time, computational resource usage, and stability across executions. The results reveal consistent differences in the operational behavior of the analyzed approaches, indicating that the execution architecture of each tool significantly influences scenario provisioning. This work contributes to expanding the empirical understanding of the use of IaC in container-based SDN emulation environments deployed and executed in the cloud.